2021
DOI: 10.1002/adfm.202104602
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Guidable Proteinaceous Adhesive Microbots for Targeted Locoregional Therapeutics Delivery in the Highly Dynamic Environment of the Esophagus

Abstract: The esophagus is a tubular-shaped muscular organ where swallowed fluids and muscular contractions constitute a highly dynamic environment. The turbulent, coordinated processes that occur through the oropharyngeal conduit can often compromise targeted administration of therapeutic drugs to a lesion, significantly reducing therapeutic efficacy. Here, magnetically guidable drug vehicles capable of strongly adhering to target sites using a bioengineered mussel adhesive protein (MAP) to achieve localized delivery o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Magnetic nanoparticles (MNPs) have become ubiquitous in biomedical applications such as therapeutic microbots, [42] hyperthermia therapy for cancer, [43,44] and SARS-CoV-2 detection strips [45] owning to their great colloidal stability, biocompatibility and thermal property. [46] In our lab, we have developed a MNPs-incorporating linear PCL-based SMP for simultaneous thermo-chemotherapy.…”
Section: Laser Actuation Simulations Of Smp Stringmentioning
confidence: 99%
“…Magnetic nanoparticles (MNPs) have become ubiquitous in biomedical applications such as therapeutic microbots, [42] hyperthermia therapy for cancer, [43,44] and SARS-CoV-2 detection strips [45] owning to their great colloidal stability, biocompatibility and thermal property. [46] In our lab, we have developed a MNPs-incorporating linear PCL-based SMP for simultaneous thermo-chemotherapy.…”
Section: Laser Actuation Simulations Of Smp Stringmentioning
confidence: 99%
“…Despite the esophagus can be easily accessed through oral administration, targeted therapies for esophageal cancer face the challenge of the fluid gravity factor due to rapid transit times and low uptake as well as weak adhesion of the drugs. Inspired by marine mussels, Choi et al 100 reported a magnetically guidable drug vehicles that were capable of strongly adhering to target sites using a bioengineered mussel adhesive protein to achieve localized delivery of therapeutic drugs against the hydrodynamic physiological conditions (Figure 8f). For mice without an applied magnetic field around the anterior neck tissue the particles (drug vehicles) were detected in the lower GI track after oral administration.…”
Section: Acs Nanomentioning
confidence: 99%
“…(f) Protein-based adhesive soft microrobots, that can overcome the short dwell time of drugs in the esophagus to enable targeted drug delivery. Reproduced with permission from ref . Copyright 2021 Wiley-VCH.…”
Section: Delivery In Gastrointestinal Tractmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral delivery refers to the route of pharmaceutical absorption through the digestive tract for local or systemic therapy. Drug formulations are orally delivered to reach the buccal cavity 1 , oesophagus 2 , stomach 3 and intestine 4,5 . As one of the most common drug delivery methods, oral delivery offers a non-invasive, low-cost route of administration with high drug versatility and patient compliance 6,7 (Fig.…”
Section: Introductionmentioning
confidence: 99%